1998
DOI: 10.1016/s0741-5214(98)70006-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ultrasound guided thrombin injection: A new method for treating postcatheterization femoral pseudoaneurysms

Abstract: Percutaneous ultrasound guided thrombin injection appears to be a safe and expeditious method for treating postcatheterization femoral pseudoaneurysms. It has significant advantages with respect to ultrasound guided compression repair or surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
172
1
14

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(193 citation statements)
references
References 21 publications
6
172
1
14
Order By: Relevance
“…No significant differences in success were observed with respect to pseudoaneurysm size (P = 0.30) and lobe number (P = 0.17). These results are parallel to the results of Kang et al (7). However, higher failure rates with complex multicompartmental pseudoaneurysms have been reported (9).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…No significant differences in success were observed with respect to pseudoaneurysm size (P = 0.30) and lobe number (P = 0.17). These results are parallel to the results of Kang et al (7). However, higher failure rates with complex multicompartmental pseudoaneurysms have been reported (9).…”
Section: Discussionsupporting
confidence: 87%
“…The addition of sufficient amounts of thrombin to anticoagulated blood will reliably induce thrombosis because the final pathway of blood coagulation is the generation of thrombin (7). Unlike compression repair, anticoagulation does not affect the success of thrombin injection (2,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators demonstrated the efficacy and safety of an alternative approach to the repair of postcatheterization pseudoaneurysms using US guided thrombin injection [11][12][13]. Naidu et al [14] reported a case of percutaneous embolization of a lumbar pseudoaneurysm in a patient with type IV Ehlers-Danlos syndrome using nbutyl cyanoacrylate and coils via a US guided lumbar approach.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was described by Kang et al 13 , countless subsequent publications have shown that treatment with thrombin is effective, rapid and comfortable for the patient and has an efficacy rate of 96% to 100% 14,15 . Small pseudoaneurysms, especially those with diameters smaller than 2.0 cm, can be treated conservatively and spontaneous thrombosis can be expected 16,17 .…”
Section: Discussionmentioning
confidence: 99%